Analisis Faktor-Faktor Optimalisasi Kinerja Nu Care–Lazisnu Desa Bumi Pratama Mandira - Rieke Oktaviyanti (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2025)
This study analyzes the factors influencing the performance optimization of NU Care-LAZISNU in Bumi Pratama Mandira Village, Sungai Menang District, Ogan Komering Ilir Regency. The research is driven by the sub-optimal performance of NU Care-LAZISNU, as indicated by low community participation in the collection and distribution of zakat, infak, and alms (ZIS) funds. The purpose of this research is to identify and analyze key factors such as institutional capacity, management quality, transparency, accountability, and community awareness and participation. A qualitative method with a case study approach was used, with data collected through in-depth interviews, observation, and documentation. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The results indicate that performance optimization is hindered by limited community outreach, lack of competent human resources, non-digitized administrative systems, and low public trust. The study suggests the need for managerial training, technological integration in administration, and strategic communication to enhance public involvement. Improving these aspects is expected to strengthen NU Care-LAZISNU’s role as a professional and trustworthy Islamic philanthropic institution.